IDENTIFYING AND MEASURING THE WEIGHTS OF HALAL COMPLIANCE RATING (HCR) COMPONENTS OF BEST HALAL PRACTICES BY APPLYING AHP METHOD - Azam, Md Siddique E; Abdullah, Moha Asri; Ahmad, Anis Najiha (IJIBE (International Journal of Islamic Business Ethics), 2021)
The halal industry in restaurant chain is lacking a rating system that would help the consumers to choose their preferences and enhance the halal integrity. In this regard, as a first step to develop a halal compliance rating (HCR) tool, the objective of this research is to identify and select the components of best halal practices for restaurants. This was achieved by reviewing existing relevant rating systems, standards, and research papers. The selected ten components were weighed by applying Analytic Hierarchy Process (AHP) method of decision making through the participation of 15 experts where the maximum priority was given to ‘Hygiene and Food Safety (HFS)’ component with a weightage of 22.3%. The least priority was given to ‘Branding, Packaging, and Labelling (BPL)’ with a weightage of 4.4%. The consistency ratio was checked as 0.015. Additionally, the study investigates the auditable and measurable areas of the selected ten HCR components.